The More Kids, the Less Mom's Divvy: Impact of Childbirth on Intrahousehold Resource Allocation - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2008)
We investigate how the impact of childbirth on intrahousehold allocation for married Japanese couples. We developed reduced‐form and structural‐form specifications from a unified theoretical framework. Under a weak set of assumptions, we can focus on private goods to track the changes in intrahousehold resource allocation. Our estimation results show that that allocation of resources within household tend to move to the disadvantage of women after a childbirth. One additional child is associated with a reduction in the wife's private expenditure share. Our estimation results reject the income-pooling hypothesis, and show that women are more risk averse than men.